The Application of Montmorillonite (MMT), Halloysite (HNT), and Carbon Nanotubes (CNT) in Toughened Polyethylene Terephthalate Glycol/Polycarbonate (PETG/PC) Blends: The Critical View on the Use of Nanosized Fillers as Phase Structure Modifiers - Markowski, Mateusz; Piasecki, Adam; Andrzejewski, Jacek (Polymers, 2025)
The subject of the conducted study was primarily focused on the development of a new type of polymer blend modified with the use of nanosized fillers. The research concept involved the use of polycarbonate/polyethylene terephthalate glycol (PETG/PC) blends modified with the EBA-GMA impact modifier (ethylene–butylene–acrylonitrile copolymer) and three different types of nanofillers: montmorillonite (MMT), halloysite (HNT), and carbon nanotubes (CNT) of two types. The combination of PC, PETG, and EBA phases was used in order to achieve enhanced mechanical performance and stable processing properties. The results of the conducted study revealed that for the toughened PETG/PC/EBA blends, the impact resistance was strongly improved from the reference by 1.5 kJ/m2 to 15 kJ/m2. However, the results for the nanocomposites revealed that the MMT and HNT additions were limiting the impact strength. In contrast, the Charpy test results for CNT were again close to 15 kJ/m2. The results of the thermal resistance measurements again revealed more favorable properties for CNT-modified PETG/PC/EBA blends.